Pengaruh Kualitas Produk terhadap Kepuasan Konsumen Dua Elang Makmur - Sirojudin, Wildan; Muttaqin, Muhammad Zaenal; Tarmizi, Muhammad Mulya (An Nuqud Journal of Islamic Economics, 2024)
The basis for this study arises from the remarkable growth observed in the MSME sector of Indonesia in 2022, amounting to a total of 8.71 million units. Concurrently, the market has become more fiercely competitive. To address this situation, it is essential for MSMEs to develop marketing strategies that align with their specific business circumstances, enabling them to uphold their competitive edge and effectively contend with similar enterprises. The primary objective of this study is to assess the impact of product quality on consumer satisfaction within the Dua Elang Makmur company, utilizing quantitative research methodologies. The research sample consists of 100 consumer participants who have utilized products from Dua Elang Makmur. Data collection involves the distribution of questionnaires and direct interviews with consumers. Data analysis employs validity testing techniques, reliability tests, and chi-square tests to scrutinize the correlation between product quality variables. The research findings on the influence of product quality on consumer satisfaction at Dua Elang Makmur are substantiated by the t-count>t-table value of 235.305>1.66055, indicating statistical significance. With a Chi-square result of 0.001<0.05, it can be inferred that the alternative hypothesis (Ha) is accepted, while the null hypothesis (Ho) is rejected. In essence, this implies a discernible impact of product quality on consumer satisfaction at Dua Elang Makmur